Cell-Derived Vesicles for Antibiotic Delivery-Understanding the Challenges of a Biogenic Carrier System - Heinrich, Eilien; Hartwig, Olga; Walt, Christine; Kardani, Arefeh; Koch, Marcus; Jahromi, Leila Pourtalebi; Hoppstaedter, Jessica; Kiemer, Alexandra K.; Loretz, Brigitta; Lehr, Claus-Michael; Fuhrmann, Gregor (Small, 2023)
Recently, extracellular vesicles (EVs) sparked substantial therapeutic interest, particularly due to their ability to mediate targeted transport between tissues and cells. Yet, EVs' technological translation as therapeutics strongly depends on better biocompatibility assessments in more complex models and elementary in vitro-in vivo correlation, and comparison of mammalian versus bacterial vesicles. With this in mind, two new types of EVs derived from human B-lymphoid cells with low immunogenicity and from non-pathogenic myxobacteria SBSr073 are introduced here. A large-scale isolation protocol to reduce plastic waste and cultivation space toward sustainable EV research is established. The biocompatibility of mammalian and bacterial EVs is comprehensively evaluated using cytokine release and endotoxin assays in vitro, and an in vivo zebrafish larvae model is applied. A complex three-dimensional human cell culture model is used to understand the spatial distribution of vesicles in epithelial and immune cells and again used zebrafish larvae to study the biodistribution in vivo. Finally, vesicles are successfully loaded with the fluoroquinolone ciprofloxacin (CPX) and showed lower toxicity in zebrafish larvae than free CPX. The loaded vesicles are then tested effectively on enteropathogenic Shigella, whose infections are currently showing increasing resistance against available antibiotics.
CRIS-Team WoS Importer:2023-04-14